Transformation of the youth technology entrepreneurship system into a sustainable model of the country's innovative development - Ustaev, R. M.; Kazachenko, E. K.; Murzakanova, I. Kh; Chesnokov, V. D.; Elbyakov, A. P. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The research focuses on designing a management model for supporting youth technological entrepreneurship in the Russian Federation as the basis for innovative socially oriented development of the national economy in modern conditions of digital transformation. Goal. The analysis of existing models of youth technological entrepreneurship in Russia in order to identify ways to transform them into a sustainable model in the context of the accumulation of determinants of social sustainability and "hybrid" employment, contributing to innovative development, the creation of an effective ecosystem, as well as taking into account future trends in technological progress and the needs of the Russian economy. Materials and methods. The research methodology is based on a systematic and holistic approach. The methods of dialectics and synergetics, subject-logical, functional and situational analysis are used as a research tool. Results and discussion. In the course of the research, conceptual provisions on the need to develop a management model for supporting youth technological entrepreneurship in the Russian Federation were formulated. The motivators for entrepreneurial activity of modern youth have been identified. An algorithm for the transformation of the youth technological entrepreneurship system into a sustainable model of innovative development of the country and the expected results of the implementation of this algorithm are proposed. It is determined that the problem of the territorial economy is the relatively low level of employment and activity of young people in technological entrepreneurship, limiting the possibilities of economic growth in Russia, which is especially important due to the exhaustion of factors based on extensive exploitation of resources against the background of the development of the digital economy and the turbulent conditions of the external environment determined by sanctions pressure. Conclusion. Youth technology entrepreneurship is an actively growing sector with high socio-economic potential. However, modern trends require the increasing development and formation of entrepreneurial skills and sought-after professional competencies among the younger generation